Comparison Study of Three Common Technologies for Freezing-Thawing Measurement. (11th May 2010) - Yu, Xinbao; Zhang, Bin; Liu, Nina; Yu, Xiong (Bill)
Abstract : This paper describes a comparison study on three different technologies (i.e., thermocouple, electrical resistivity probe and Time Domain Reflectometry (TDR)) that are commonly used for frost measurement. Specially, the paper developed an analyses procedure to estimate the freezing-thawing status based on the dielectric properties of freezing soil. Experiments were conducted where the data of temperature, electrical resistivity, and dielectric constant were simultaneously monitored during the freezing/thawing process. The comparison uncovered the advantages and limitations of these technologies for frost measurement. The experimental results indicated that TDR measured soil dielectric constant clearly indicates the different stages of the freezing/thawing process. Analyses method was developed to determine not only the onset of freezing or thawing, but also the extent of their development. This is a major advantage of TDR over other technologies.